ANALISIS PERBANDINGAN KADAR FLAVONOID TOTAL TEH HIJAU DAN TEH HITAM DENGAN MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Antonia Vani Kurniawati; .A.K Pramushinta; A.S. Sinulingga; Novamei Indriani (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Tea leaves (Camellia sinensis) are a functional plant that is useful for preventing cancer, maintaining immunity and preventing premature aging. Flavonoids are one of the largest groups of polyphenols which are active compounds from tea leaves (Camellia sinensis). This study aims to determine the total flavonoid content of green tea leaf extract and black tea leaf extract using 2 extraction methods, namely maceration with 96% ethanol solvent and infusion using water solvent. The method in this research uses qualitative tests (Wilstarter cyanidin and NaOH 10%) and quantitative tests (UV-Vis Spectrophometry) and conclusions will be drawn using the SPSS statistical test T (independent)-test. The results of the qualitative test using the starter cyanidin and 10% NaOH were positive for containing flavonoids due to a reddish color change. In the quantitative test, the assay was carried out using UV-Vis spectrophotometry with a wavelength of 434 nm. In this study, the total flavonoid content obtained in the green tea maceration method was 15.728% w/w ± 0.209, black tea maceration 13.357% w/w ± 0.737, green tea infusion 4.153% w/w ± 0.124 and black tea infusion 3.320% w /b ± 0.352. There is a significant difference between green tea and black tea using both the infusion and maceration methods as shown by a sig value ≤ 0.05.